2010
DOI: 10.2215/cjn.05960809
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care Preferences and Needs

Abstract: Background and objectives: Despite high mortality rates, surprisingly little research has been done to study chronic kidney disease (CKD) patients' preferences for end-of-life care. The objective of this study was to evaluate end-of-life care preferences of CKD patients to help identify gaps between current end-of-life care practice and patients' preferences and to help prioritize and guide future innovation in end-of-life care policy.Design, setting, participants, & measurements: A total of 584 stage 4 and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
570
6
24

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 561 publications
(621 citation statements)
references
References 36 publications
21
570
6
24
Order By: Relevance
“…16 It plays out in daily medical practice through the process of informed consent. Despite the stated emphasis on patient autonomy and its corollary, shared decision making, studies show that HD patients frequently do not feel empowered to make an informed and autonomous choice 17 and feel they have no choice but to start HD treatment. 15,18 According to surveys and interviews of patients with ESRD, many do not know their prognosis and do not recall alternatives being offered, 17,19 despite preferring to receive detailed information.…”
Section: Respect For Autonomy: Patients Are Often Provided Neither Inmentioning
confidence: 99%
See 3 more Smart Citations
“…16 It plays out in daily medical practice through the process of informed consent. Despite the stated emphasis on patient autonomy and its corollary, shared decision making, studies show that HD patients frequently do not feel empowered to make an informed and autonomous choice 17 and feel they have no choice but to start HD treatment. 15,18 According to surveys and interviews of patients with ESRD, many do not know their prognosis and do not recall alternatives being offered, 17,19 despite preferring to receive detailed information.…”
Section: Respect For Autonomy: Patients Are Often Provided Neither Inmentioning
confidence: 99%
“…Despite the stated emphasis on patient autonomy and its corollary, shared decision making, studies show that HD patients frequently do not feel empowered to make an informed and autonomous choice 17 and feel they have no choice but to start HD treatment. 15,18 According to surveys and interviews of patients with ESRD, many do not know their prognosis and do not recall alternatives being offered, 17,19 despite preferring to receive detailed information. 20 Instead, patients recount being "rushed" 21 and pressured 17 into treatment at a time when they are too sick to process information and without a chance to discuss options with loved ones.…”
Section: Respect For Autonomy: Patients Are Often Provided Neither Inmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Studies have shown that patients with ESRD have limited knowledge of their prognosis and that few have been presented with alternative treatment options. 10,11 In a recent Canadian study, two-thirds of patients with chronic kidney disease (CKD) indicated that they chose HD over supportive care because it was their physician's (52%) or family's (14%) wish, and 61% of these dialysis patients regretted having started HD. 11 These findings are similar to those of a small qualitative study that showed that at 6 months after the start of HD, only 45% of patients found HD acceptable and that the symptom burden was higher at 6 months than at initiation of dialysis treatment.…”
Section: Trends In the Use Of Hd In Elderly Patientsmentioning
confidence: 99%